EFEKTIFITAS DUPONT ANALYSIS UNTUK MENILAI PROFITABILITAS PERUSAHAAN ASURANSI JIWA NASIONAL - I Nyoman Winata (Premium Insurance Business Journal, 2023)
This research aims to analyze the description of the financial condition of the DuPont analysis of national life insurance companies, and to analyze the impact of the financial condition of DuPont analysis on the performance of national life insurance companies. The data is taken from financial reports for 4 (four) years from 2016 - 2019, which have been published which are data before the Covid-19 pandemic, via the website of each company. The research method used is descriptive qualitative with a case study approach on 10 (ten) national life insurance companies that have assets of more than IDR 1 trillion. The research samples are Return on Equity (ROE), Return on Assets (ROA), Total Assets Turn Over (TATO), Net Profit Margin (NPM), and Debt Ratio (DR). Meanwhile, data analysis was carried out by: tabulating data, performing calculations and grouping DuPont analysis, interpreting to determine the level of company profitability, and drawing conclusions on the results achieved. The results of the study show that the financial condition of national life insurance companies using DuPont analysis is generally less effective and efficient. The company has not utilized its resources fully, effectively and efficiently in terms of achieving maximum sales results, and the company still uses a lot of debt for its investment. Keywords: Effectiveness, DuPont Analysis, and Profitability